Inovasi Kreasi Melalui Pendidikan untuk Anak sebagai Generasi Bangsa Masa Depan - Adia, Muhamad; Gita, Yuda (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service activity is to be creative through education for children as the nation's generation. The methods used include: 1) outreach to the village community or village officials; 2) activities carried out by Sanggar Sejahtera; and 3) learning English. The results of the activities achieved included: 1) Children's Studio activities in Jabung Village, Malang Regency. Through positive activities carried out according to a predetermined schedule, younger siblings are able to learn to share the time they have. The activities that are often carried out are discussions, making short videos to be able to provide lessons widely by sharing these videos on social media. In addition, the Children's Studio also often holds performances during major holidays, such as Independence Day, National Children's Day, and other celebrations. However, during this pandemic, the studio's activities were limited and they could only share lessons with other younger siblings through learning videos that had been made and uploaded to Sanggar Anak's social media. So that the negative activities towards children that we usually encounter in Jabung Village are slowly decreasing and even have to disappear; and 2) English learning activities. Through the learning activities that we carried out, the students from the studio were interested in participating in learning English. Some younger students in the studio never had English lessons at Elementary School (ES) or even Junior High School (JHS). In carrying out learning activities, we try to make learning active and fun by providing games as a form of repeating the lessons that have been given. We also still provide the basics of understanding English so that younger siblings don't feel confused. This makes them understand the importance of mastering languages ​​other than their mother tongue and regional languages.